Ecolinguistic sustainability of Spanglish and Chinglish communities - Semenova Marina (E3S Web of Conferences, 2023)
Spanglish and Chinglish as two most popular ‘Glishes’ have developed to a phase when we can seriously consider their sustainability issue, which provides an extensive and stable use of various loinguistic mechanisms built into thier language structure. The paper aims at analizing such trsnalingual mechanisms and corresponding code-switching functions from the perspaectuve of ecolinguistics. The research is base on two corpora of Spanglish and Chinese code-switches, which are then analyzed applying the methods of linguistic, componential, distribution and statistical analysis. Both epistemologically and deductively the paper demonstrates the two most vivid categories of code-switches both in Spanglish and Chinese: stylistic play of words based mainly on semantic borrowing, and translingual allusions and idioms used in Twitter messages over the period between 2017 and 2022. The study shows a certain correlation across the ‘Glishes’ as well as a degree of fluctuation in the corpora-based statistical data. This might involve a different sustainability weight of Spanglish and Chinglish in globalized communities. The paper concludes that the ecolinguistic monitoring of translingual communities is vitally important as we witness an influence redistribution process on the global scale.